The Effectiveness of the Risk-Based Approach in Protecting E-Governance from Cyber Corruption -An Analytical Study in Light of Algerian Legislation- (Alijtihed Journal on Legal and Economic Studies, 2026)
This research analyzes the risk-based approach as a key modern mechanism adopted by the Algerian legislator to combat corruption within the framework of digital governance. It focuses on the preventive role of public administration and highlights the shift in criminal policy from punishment toward proactive detection of financial and administrative crimes through specialized legal and technical frameworks.The study concludes that the effectiveness of this approach depends on strengthening electronic legislation and enhancing digital oversight. It also emphasizes the importance of involving civil society in reporting corruption, supporting digital platforms, and simplifying preventive monitoring tools to ensure transparency, efficiency, and the proactive prevention of corruption